SPE Annual Technical Conference and Exhibition 1992
DOI: 10.2118/24935-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gravity and Viscous Crossflow on Hydrocarbon Miscible Flood Performance in Heterogeneous Reservoirs

Abstract: Injected solvent composition is a key parameter in the design of hydrocarbon miscible floods. Economic optimization of a field flood requires consideration of the effect of solvent composition on flood performance at the reservoir-scale. In this study, a compositional simulation approach was used to study the effects of permeability heterogeneity, fluid crossflow, and phase behavior on displacement performance in two-dimensional, finegrid (x-z) cross-sections. Results of secondary and tertiary solvent flood si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…1.48). Channeling occurs only when the 85 percent enriched gas and three-point weighting is used because the denser gas reduces gravity crossflow to the top lower permeability layers (these results are similar to Pande (1992).…”
Section: Resultssupporting
confidence: 61%
“…1.48). Channeling occurs only when the 85 percent enriched gas and three-point weighting is used because the denser gas reduces gravity crossflow to the top lower permeability layers (these results are similar to Pande (1992).…”
Section: Resultssupporting
confidence: 61%
“…Field-scale simulations show that near-miscible solvents are attractive because of improved sweep over miscible solvents (Pande 1992). Burger et al (1994) showed that economically optimum enrichment in high-viscosity-ratio secondary gas floods could be operated at pressures below the MMP.…”
Section: Introductionmentioning
confidence: 99%
“…Field-scale simulations show that near-miscible solvents are attractive because of improved sweep over miscible solvents (Pande 1992). Burger et al (1994) showed that economically optimum enrichment in high-viscosity-ratio secondary gasfloods could be operated at pressures below the MMP.…”
mentioning
confidence: 99%